Age-Related Morphological and Morphometrical Changes in the Goat Brain: A Gross Anatomical Study - Pratibha Kumari; Avnish Kumar Gautam; Sanjay Kumar Bharti; Manoj Kumar Sinha; Manoj Kumar Singh (Indian Journal of Veterinary Anatomy, 2026)
The present study was conducted on the brain of the black Bengal goat irrespective of sex. Whole experiment was divided into two groups i.e Group-I comprise of six young goats (6 to 8 months of age) and Group- II comprise of six adult goats (above 8 months of age). The gross biometrical observation of cerebrum and cerebellum were recorded. The cerebrum was the largest part of the whole brain in both age groups of Black Bengal goat. Its shape varied from triangular to oval in outline. The cerebellum was the largest part of the rhombencephalon situated behind the cerebrum and dorsal to the pons and medulla oblongata. The cerebellum was oval with wider dimension along transverse axis. In mid- sagittal section of cerebellum, ten distinct lobules were observed in both the age groups of goats. The length as well as width of cerebrum was found to be increased with the advancement of age from group I to group II, but no significant differences were observed in length and width of cerebrum of goat from Group I to II.